Works councils and workers' party preferences in Germany - Uwe Jirjahn; Thi Xuan Thu Le (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2023)
Research on the consequences of works councils has been dominated by economic aspects. Our study provides evidence that works councils have nonfinancial consequences for civic society that go beyond the narrow boundaries of the workplace. Using panel data from a large sample of male workers, the study shows that works councils have an influence on workers' party preferences. The presence of a works council is negatively associated with preferences for extreme right-wing parties and positively associated with preferences for the Social Democratic Party and The Left. These results holds in panel data estimations including a large set of controls and accounting for unobserved individual-specific factors. Our findings fit the notion that workplace democracy increases workers' generalized solidarity and their awareness of social and political issues.
Keywords: D72; J51; J52; J58; 330; Workplace democracy; worker participation; political spillover; party identification